English Teachers’ Perception on Scientific Approach Implemented on English Curriculum 2013 in Kendari - Devi, Putu Chintya; Hanna, Hanna; Kamaluddin, Kamaluddin (Universitas Halu Oleo, 2021)
The 2013 curriculum emphasizes a new learning process to improve the quality of the educational system in Indonesia. The 2013 curriculum comes with a new performance, which emphasizes the implementation of a scientific approach in all subjects including English. The purpose of this research is to describe the perception of English teachers on the Scientific Approach implemented on English curriculum 2013 in Kendari. The subjects of this research were 40 English teachers of Junior High School in Kendari. This research used a quantitative method with a survey approach. The data of this research were collected by using questionnaire perception that was adapted from Han Hui (2010). The data were analyzed by using descriptive statistics to find out the mean score of each respondent. The perception of English teachers was analyzed based on the cognitive, psychomotor, and affective aspects. The questionnaire consists of 25 statements that were divided into four indicators; first is about the understanding of learning by using a scientific approach, second is about learning readiness by using a scientific approach, third is about the implementation of scientific approach in the learning process, and the last is the evaluation of a scientific approach in learning. The result of this research shows that English teachers have a positive perception of the Scientific Approach implemented in the 2013 curriculum. It is proven by the result of the mean scores of cognitive aspects are 3.65, the psychomotor aspect gets 3,60 of the mean score and the affective aspect get 3,28 of the mean score. Meanwhile, the overall mean score was 3,55 categorized as a very high level that indicated the English teachers have positive perception or strongly agree with the scientific approach implemented in the 2013 curriculum.